Petroselinum crispum extract ameliorates scopolamine-induced cognitive dysfunction: role on apoptosis, inflammation and oxidative stress - Göksel Şener; Gözde Karakadıoglu; Dilek Ozbeyli; Seren Ede; Refiye Yanardag; Ozlem Sacan; Asli Aykac (Food Science and Human Wellness)
This study was designed to investigate whether Petroselinum crispum (PC) extract has protective effects on the brain in the scopolamine-induced Alzheimer’s disease (AD) rat model. The rats were divided into; control, scopolamine (1 mg/kg, i.p.), galantamine (1.5 mg/kg, i.p.) and PC extract (2 g/kg, p.o.)-treated scopolamine groups. On day 14, the novel object recognition test (NORT) and Morris water maze test (MWMT) were performed and then the rats were sacrificed. Scopolamine-induced cognitive impairments observed in the NORT and MWMT, significantly improved with PC extract and galantamine treatments. Scopolamine reduced M1 receptor expression, Bcl-2/Bax ratio, and glutathione levels in the hippocampus and frontal cortex, while malondialdehyde levels, caspase-3/9 expressions, and acetylcholinesterase (AChE) activity were found to be increased. On the other hand, PC and galantamine treatments reversed these changes. In conclusion, PC extract has shown an ameliorative effect on the spatial and recognition memory, M1 receptor expression, apoptosis, oxidative stress, and increased AChE activity. Thus, it was concluded that PC could prevent AD-like conditions and can be used as a functional food. However, since animal models do not completely mimic those of humans, based on the data obtained in this study, the importance of PC on human AD should be demonstrated in future studies.